Determinação de resíduos de agrotóxicos em uva empregando método QuEChERS e UHPLC-MS/MS - Cassól, Ricardo Ramos Corrêa (2019)
Grapes, classified as fruits play important role in human diet and nutrition. They are sources of vitamins, polyphenols, essential amino acids, and a wide range of health benefits. Grapes are extremely rich in pigments, such as anthocyanins and anthocyanidins, responsible for conferring color, a characteristic used as a parameter of maturity and quality. The instinctive preferences and the search for a healthier life lead to the practice of eating naturally colored foods. Although, like many other crops, grapes are susceptible to pest attack, such as fungi and other diseases, and the application of plant health products is a common practice in agriculture to circumvent this problem and increase productivity. Therefore, it is necessary to monitor the products intended for consumption, which may pose risks to human health, resulting from chronic dietary exposure. However, the sample matrix contains abundant quantities of anthocyanins, requiring a preliminary sample preparation step capable of providing clean extracts and suitable recoveries of the compounds of interest. The main objective of this work was to optimize the cleaning of sample preparation through the use of different dilution volumes through the dilution and shoot technique for the removal of pigments derived from the different anthocyanins present in extracts from grape samples. The experiments were evaluated by gravimetric tests, and qualitative analysis by the GC-MS / MS chromatographic system and by high performance liquid chromatography with ultraviolet / visible detection (HPLC-UV / Vis). After optimization, a multi-residue method was developed and validated for the determination of 36 agrochemicals in grapes using modified QuEChERS citrate method and evaluated by ultra high-performance liquid chromatography coupled to mass-mass spectrometry (UHPLC-MS / MS). allowed the accomplishment of the analyzes with high selectivity and sensitivity. The extracts were cleaned using the dilution and shoot technique, applying different dilutions of the extract in 2, 5, 10, 20 and 40x, the latter being the method that presented better efficiency in the removal of coextractives and adequate recoveries of the compounds. The validation results were satisfactory with recoveries between 70 and 120% and RSDs ≤20%. The curves were prepared in the matrix extract, due to the presence of a strong matrix effect for most of the compounds. The limits of detection and quantification were 7 and 25 μg kg-1, respectively. The proposed method proved to be adequate for the determination of multi-residues of pesticides in grapes, as well as, the dilution stage of the extracts demonstrated satisfactory efficiency, detectability and selectivity to the method and also in the application of 20 samples since all the parameters suggested for the validation chromatographic methods are within the limits.